2005
DOI: 10.1007/s00464-004-2170-y
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of ambulatory laparoscopic cholecystectomy: Training economic, and patient benefits

Abstract: Our results for ALC compare favorably with published series. In addition, we have demonstrated that the operation can be performed safely by HST under direct supervision without compromising operating lists or safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
35
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 22 publications
11
35
0
1
Order By: Relevance
“…The success rate (90%) and re-admission rate (10%) in our study are comparable to that of other studies which performed DS LC or ambulatory LS, (5,14,15) with a success rate of 86%-95% and re-admission rate of 1.5%-8%. Postoperative nausea and vomiting(PONV) remained a frequent reason for unplanned admission after ambulatory LC.…”
Section: Discussionsupporting
confidence: 87%
“…The success rate (90%) and re-admission rate (10%) in our study are comparable to that of other studies which performed DS LC or ambulatory LS, (5,14,15) with a success rate of 86%-95% and re-admission rate of 1.5%-8%. Postoperative nausea and vomiting(PONV) remained a frequent reason for unplanned admission after ambulatory LC.…”
Section: Discussionsupporting
confidence: 87%
“…The conversion rate of 1% found in this study is similar to those found in other studies [4,11,13]. Median operating time was not affected by the operations being converted hence it did not influence the result that operating time was a significant predictor of unexpected admission.…”
Section: Symptomatic Cholecystolithiasis 434supporting
confidence: 89%
“…The majority were treated conservatively with few episodes of major complications needing intervention such as laparoscopic re-surgery or stone extraction with ERCP. The results are comparable to those found in other studies [1,4,7,8,13]. Boehme et al [6] have looked into the relation between co-morbidity and postoperative resource utilization after LC and OC finding that certain comorbid conditions significantly increase utilization of postoperative resources including readmissions.…”
Section: Symptomatic Cholecystolithiasis 434supporting
confidence: 82%
“…Laparoscopic cholecystectomy is often conducted as day surgery [27]. The surgery involves creation of pneumoperitoneum and a reverse Trendlenberg position with lateral tilt.…”
Section: Sad In Laparoscopic Cholecystectomymentioning
confidence: 99%